Effect of OnDuty™ herbicide on weed populations and rice yields in selected rice fields, Melaka, Malaysia - Mardiana-Jansar K.,; Bajrai F.S.M.,; Muhamad Safwan Ishak,; Ismail B.S., (Penerbit Universiti Kebangsaan Malaysia, 2019)
The effect of the herbicide OnDuty™ herbicide (imazapic + imazapyr) on the weed population and growth of rice plants was investigated. The study was conducted at Kampung Parit Penghulu Benteng, Sungai Rambai, Melaka for two seasons (season 1 (September–December 2015) and season 2 (February-May 2016)) to identify the weed population and determine the paddy yield components in the paddy field with OnDuty™ application. Six species under four families, namely, Plantaginaceae (Bacopa monnieri), Araceae (Alternanthera sessilis), Cyperaceae (Fimbristylis miliacea, Cyperus iria, Cyperus difformis) and Poaceae (Paspalum distichum, Leptochloa chinensis, Oryza sativa (weedy rice), Echinochloa glabrescens), were found in the rice fields. A. sessilis and B. monnieri are the most abundance weeds found in both seasons. During season one, A. sessilis was the most dominant weed compared with other species. Higher dosage of OnDuty™ up to 300 g ai/ha OnDuty™ (double recommended dose) did not affect the relative density of weeds and weedy rice can be controlled at half recommended dose. The Clearfield® production system offers control of many weeds especially parasitic weed which missed by other herbicides and adds an effective weed-control tool to rice. In season two, weedy rice was not detected. The yield of rice was significantly higher in plots treated at 300 g a.i/ha OnDuty™ for both seasons. Thus, OnDuty™ can effectively control weedy rice at half recommended dose and increase rice yield at double recommended dose.